Progress and Evaluation of Scientific Skills through the Use of the Scientific Inquiry Methodology in Initial Education - Morales Silva, Tatiana Aura (2024)
This paper presents in three cohorts, whose objective was to analyze the progress of scientific skills in children, a proposal for didactic innovation in early childhood education. The investigators carried out practical workshops based on the scientific research methodology and focused on the development and evaluation of their scientific skills according to the Chilean curricular framework. Hence, the qualitative technique of drawing was used to demonstrate the learning and perceptions of the infants about the natural sciences. In the first instance, the authors evaluated the children's perception of science. Subsequently, an evaluation of the scientific process was carried out at the beginning and at the end of the proposal. The results revealed a conceptual change in the drawings about who does the science and where this learning occurs. In addition, the investigators noticed significant advances in observation, prediction, and communication skills, which were evaluated progressively throughout the process by reviewing the preschool children's workbooks. These results support the use of scientific inquiry as an effective tool for the development of knowledge in natural sciences and the promotion of skills necessary for their understanding in the field of initial education. Future studies must investigate teaching practices oriented towards inquiry and the real appropriation of scientific skills articulated at subsequent levels of training, thus providing a sense of continuity and strengthening prior and initial learning in primary education.